Sequence of Events Underlying the Allosteric Transition of Rod Cyclic Nucleotide–gated Channels - Sunderman, Elizabeth R. (The Rockefeller University Press, 1999)
Activation of cyclic nucleotide–gated (CNG) ion channels involves a conformational change in the channel protein referred to as the allosteric transition. The amino terminal region and the carboxyl terminal cyclic nucleotide–binding domain of CNG channels have been shown to be involved in the allosteric transition, but the sequence of molecular events occurring during the allosteric transition is unknown. We recorded single-channel currents from bovine rod CNG channels in which mutations had been introduced in the binding domain at position 604 and/or the rat olfactory CNG channel amino terminal region had been substituted for the bovine rod amino terminal region. Using a hidden Markov modeling approach, we analyzed the kinetics of these channels activated by saturating concentrations of cGMP, cIMP, and cAMP. We used thermodynamic mutant cycles to reveal an interaction during the allosteric transition between the purine ring of the cyclic nucleotides and the amino acid at position 604 in the binding site. We found that mutations at position 604 in the binding domain alter both the opening and closing rate constants for the allosteric transition, indicating that the interactions between the cyclic nucleotide and this amino acid are partially formed at the time of the transition state. In contrast, the amino terminal region affects primarily the closing rate constant for the allosteric transition, suggesting that the state-dependent stabilizing interactions between amino and carboxyl terminal regions are not formed at the time of the transition state for the allosteric transition. We propose that the sequence of events that occurs during the allosteric transition involves the formation of stabilizing interactions between the purine ring of the cyclic nucleotide and the amino acid at position 604 in the binding domain followed by the formation of stabilizing interdomain interactions.